Lipid profile and health benefit of commonly consumed fresh water and sea water fish species in the population of Serbia - Đuričić Ivana; Gojković Tamara; Antonijević Biljana; Šobajić Slađana (Vojnosanitetski Pregled)
Background/Aim. Dietary intake of n-3 long-chain polyunsaturated fatty acids (LC-PUFA) is important in prevention and treatment of different diseases. In general population, the average intake of n-3 LC-PUFA is often significantly lower than recommended levels. Fish lipids are rich sources of these fatty acids, of which the most important are eicosapentaenoic (20:5 n-3, EPA) and docosahexaenoic (22:6 n-3, DHA) fatty acids. This study was designed to determine and compare fat, fatty acids and lipid quality indices in 10 commercial fish species available on the Serbian market, as well as relation between their price and nutritional value. Methods. Freshwater fish originated from the Danube River in the Belgrade Region, while seawater fish were mostly from the Adriatic Sea. A gas chromatography method was used to define fatty acids in 40 fish samples after lipid extraction. Cost-minimization analysis was conducted to assess the economic utility. Results. Seawater fish had a significantly higher value of flash lipid quality compared to the freshwater fish (p < 0.05). Value of hypercholesterolaemic fatty acids (OFA) for the freshwater group was 18.70 (17.40‒21.30) while the seawater group had a similar range of values 18.90 (17.55‒22.75). Hypocholesterolaemic fatty acids (DFA) also showed similar ranges for both groups: 68.80 (66‒70.20) for freshwater and 68.40 (64.85‒73.05) for seawater group. The ratio of DHA/EPA ranged from 1.8 for sardine samples and up to 10 for tuna samples, indicating that the amount of DHA in natural samples exceeds the amount of EPA in many cases. The values of atherogenic (AI) and thrombogenic index (TI) were lower than 1 for all analysed samples. Conclusion. Sardine and mackerel had the highest content of n-3 LC-PUFA and presented the least expensive sources of EPA and DHA. The low values of AI and TI obtained from studied fish indicate its benefits from a health point of view.